The Influence of Leadership, Motivation and Work Discipline on the Performance of Employees in the Directorate of Vocational High Schools, Ministry of Education and Culture Office - Djatmika, Gatot Hery; Ningsih, Putu Tirta Sari; Harsono, Budi; Miratunisa (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of leadership, motivation, and work discipline on employee performance at the Directorate of Vocational High Schools using the SPSS test. The data analysis method in this study uses a quantitative approach with quantitative data processing techniques using multiple regression analysis. The data collection technique used is a questionnaire. The results of this study indicate that if the t test can be seen that the results of the calculated t value are 2.402> 2.0129 or a Sig value of 0.020 <0.05, meaning that the leadership variable greatly influences the performance of employees of the Directorate of Vocational High Schools. Seen from the t test can be seen that the results of the calculated t value are 2.177> 2.0129 or a Sig value of 0.035 <0.05, meaning that the motivation variable greatly influences the performance of employees of the Directorate of Vocational High Schools. Judging from the t-test, it can be seen that the calculated t-value is 2.408 > 2.0129 or a Sig value of 0.020 < 0.05, meaning that the motivation variable has a significant effect on the performance of employees of the Directorate of Vocational High Schools. Meanwhile, seen from the F-test, it can be seen that the significance value of Leadership X1, Motivation X2, and Discipline X3 on employee performance Y is 0.000 < 0.05 and F count 66.820 > 2.80, cannot be denied because H0 is rejected, so it can be concluded that Leadership, Motivation and Discipline have an effect on employee performance.